Implementation Of Interprofessional- Colaboration (IPC) In The Community Health Center Regarding Exclusive Breastfeeding On Mothers' Knowledge, Attitudes And Exclusive Breastfeeding Achievements - Putriana, Yeyen; Pranajaya, R; Risneni, Risneni (Program Studi Kebidanan Fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Pemberian ASI eklusif dan menyusu selama minimal 2 tahun membutuhkan pengetahuan dan sikap yang positif bagi ibu. Puskesmas sebagai bagian dari pemerintah berkewajiban untuk meningkatkan capaian ASI melalui salah satunya kegiatan kelas ibu. Kelas ibu dapat dimanfaatkan untuk menerapkan interprofesional colaborasi (IPC) antara bidan, petugas imunisasi dan gizi untuk memberikan pendampingan selama menyusui.Tujuan penelitian ini untuk mengetahui efektifitas penerapan IPC bagian KIA, Imunisasi dan Gizi tentang asi eklusif terhadap pengetahuan, sikap dan capaian asi eklusif di Puskesmas Kemiling Kota Bandar Lampung tahun 2024 .Metode penelitian ini merupakan penelitian quasi eksperimen dengan one group pre dan post test. Populasi penelitian seluruh ibu menyusui yang datang ke Puskesmas Kemiling. Sampel diambil dengan menggunakan purposive sampling dan menggunakan kriteria eklusi dan inklusi. Hasil perhitungan rumus Lemeshow didapatkan 30 responden. Alat ukur yang digunakan adalah kuesioner. Media pendampingan menggunakan booklet . Analisi data menggunakan analisis univariat dan bivariat uji T dependen.Hasil penelitian di dapatkan terdapat peningkatan pengetahuan ibu sebelum dan setelah intervensi dengan V palue 0,0001 terdapat peningkatan sikap ibu sebelum dan setelah intervensi dengan V- palue 0,0002, terdapat peningkatan cakupan asi eklusif sebesar 93%. Kesimpulan penerapan IPC untuk meningkatkan pengetahuan, sikap dan capaian asi eklusif . Saran kepada Puskesmas secara kontinue memberikan pendampingan di kelas ibu untuk meningkatkan cakupan asi dan menyusu selama 2 tahun . Kata Kunci ; ASI eklusif, Capaian, IPC, Pengetahuan, Sikap, ABSTRACT Exclusive breastfeeding and breastfeeding for at least two years require knowledge and a positive attitude from mothers. Community health centers, as part of the government, are obligated to improve breastfeeding outcomes through activities such as mothers' classes. These classes can be used to implement interprofessional collaboration (IPC) between midwives, immunization officers, and nutritionists to provide support during breastfeeding.The purpose of this study was to determine the effectiveness of the implementation of the IPC section of KIA, Immunization and Nutrition regarding exclusive breastfeeding on knowledge, attitudes and achievements of exclusive breastfeeding at the Kemiling Community Health Center, Bandar Lampung City in 2024.This research method is a quasi-experimental study with one group pre- and post-test. The study population was all breastfeeding mothers who came to the Kemiling Community Health Center. The sample was taken using purposive sampling and using exclusion and inclusion criteria. The results of the Lemeshow formula calculation obtained 30 respondents. The measurement instrument used was a questionnaire. The mentoring media used a booklet. Data analysis used univariate and bivariate analysis of the dependent T test.The results of the study showed an increase in maternal knowledge before and after intervention with V-palue 0.0001, there was an increase in maternal attitudes before and after intervention with V-palue 0.0002, there was an increase in exclusive breastfeeding coverage by 93%. The conclusion of the application of IPC to improve knowledge, attitudes and achievements of exclusive breastfeeding. Suggestions to the Community Health Center continuously provide assistance in mother's classes to increase the coverage of breast milk and breastfeeding for 2 years. Keywords: Exclusive breastfeeding, Achievement, IPC, Knowledge, Attitude